Advances in cold spray : a coating deposition and additive manufacturing process - Champagne, Victor K.; Helfritch, Dennis; Hassani, Mostafa (Woodhead Publishing series in metals and surface engineering., 2023)
Advances in Cold Spray: A Coating Deposition and Additive Manufacturing Process, Second Edition reviews the fundamental processes and recent advances made in the field of cold spray. This fully updated edition now includes a special chapter on Cold Spray Additive Manufacturing, along with advancements in impact modeling and simulation that allow a better understanding of the cold spray bonding mechanisms, powder synthesis and predictive modeling to improve the engineering of cold spray powders. In addition, materials properties data is a backbone of this book because the advanced cold spray materials have proven to be comparable to wrought and enable cold spray to be incorporated into structural applications for near-net shape parts production as well as for repair. Finally, numerous modern applications of cold spray representative of the Electronics, Medical, Petrochemical, Nuclear, Aerospace, Automotive, and Additive Manufacturing industries are presented.